Transitions in product use during the implementation of the European Tobacco Products Directive: cohort study findings from the EUREST-PLUS ITC Europe Surveys. (12th September 2020) - Vardavas, Constantine I; Kyriakos, Christina N; Driezen, Pete; Girvalaki, Charis; Nikitara, Katerina; Filippidis, Filippos T; Fernández, Esteve; Mons, Ute; Przewoźniak, Krzysztof; Trofor, Antigona C; Demjén, Tibor; Katsaounou, Paraskevi A; et al.
Abstract: Background: The emergence of new types of tobacco and tobacco-related products on the European Union (EU) market has precipitated the possibility for both poly-tobacco use and transitions between products. In the EU, the regulatory environment has shifted with the implementation of the European Tobacco Products Directive (TPD) in May 2016, which may influence consumer transitions between products. Methods: The aim of this paper was to examine trends and transitions in tobacco products from 2016 to 2018 -before and after implementation of the TPD in the EU. Data come from Wave 1 (pre-TPD) and Wave 2 (post-TPD) of the EUREST-PLUS ITC Six European Country Survey, a cohort study of adults who at the time of recruitment were smokers from six EU countries- Germany, Greece, Hungary, Poland, Romania, and Spain. D ( N = 3195). Bivariate and logistic regression analyses of weighted data was conducted using SAS-callable SUDAAN Results: Overall, among those who smoked factory-made cigarettes (FM) only at Wave 1, 4.3% switched to roll-your-own tobacco (RYO) only. Among RYO only users at Wave 1, 17.0% switched to FM only, however compared to all other countries, respondents from Hungary had the highest percentage of FM only users at Wave 1 switch to RYO only at Wave 2 (18.0%). Conclusions: The most prominent transition overall was from smoking RYO exclusively at Wave 1 to smoking FM tobacco exclusively at Wave 2, however this varied across countries. As the tobacco control regulatory environment of the EU develops, it is important to continue to monitor transitions between types of products, as well as trends in cessation.